Prevalence of Vibrio spp. Infection in Shrimp and Bio-control Using Bacteriophages Isolated from Shrimp Farms in Kuching - Dalene, Lesen (Universiti Malaysia Sarawak, 2024)
Shrimp farming, a highly profitable sector in global aquaculture, has seen remarkable growth in recent years, with global shrimp consumption projected to reach US$ 74 billion by 2032. This increasing demand and the expansion of farming operations, including in Sarawak, Malaysia, highlight the sector's potential. However, the industry faces significant challenges, particularly the prevalence of vibriosis, a bacterial infection caused by Vibrio species. Contamination of food products has also increased the risk of vibriosis in humans. The widespread use of antibiotics to combat this disease has led to the rapid emergence of antimicrobial resistance (AMR) bacteria. This study presents a comprehensive investigation into the surveillance profiles and bio-control of Vibrio spp. isolated from a shrimp farm in Sarawak, Malaysia. A total of 48 (n=48) samples, including water, sediment, shrimp, and effluent, were collected from two ponds throughout the production cycle. The prevalence and quantification of Vibrio species were assessed by implementing the MPN-multiplex polymerase chain reaction (PCR) method. The findings revealed high prevalence rates, with Vibrio parahaemolyticus being the most prevalent species (97.92%), followed by Vibrio cholerae (47.92%) and Vibrio alginolyticus (25.0%). The MPN values of V. parahaemolyticus were as high as >1,100 MPN/mL or MPN/g in the water, sediment, and shrimp samples of both ponds, which are the highest among the three Vibrio species. The MPN values of V. cholerae and V. alginolyticus remained less than 1,100 MPN/mL or MPN/g in water, sediment, and shrimp samples towards the end sampling period despite starting high initially. Notably, V. parahaemolyticus exhibited an increasing trend from stocking to harvesting periods, whereas V. cholerae and V. alginolyticus showed a decreasing trend. Further analysis involved antibiotic susceptibility testing of 30 (n=30) Vibrio spp. isolates by using 18 antibiotics, revealing resistance to at least two antibiotics. Antibiotics Ceftazidime, Meropenem, Gentamicin, Tetracycline, Nalidixic acid, Norfloxacin, Ciprofloxacin, and Chloramphenicol were 100% effective against all isolates of V. parahaemolyticus, V. cholerae, and V. alginolyticus. Meanwhile, 100% of V. parahaemolyticus and V. alginolyticus isolates were completely resistant to Penicillin G and Bacitracin, whereas 100% of V. cholerae isolates exhibited resistance to Penicillin G. The MAR indices of the isolates ranged from 0.11 to 0.39. In response to the escalating antibiotic resistance, bacteriophages emerged as promising alternatives. Two novel myophages, EniLVP01 and EniLVP02, targeting V. parahaemolyticus were isolated, characterised, and found to exhibit narrow host ranges and large burst sizes of 110 and 144 phages per infected cells, respectively. Notably, they effectively prevented and reduced bacterial biofilms. In the biofilm prevention, the absorbances were reduced from 0.592 ± 0.055 to 0.218 ± 0.039 for EniLVP01 and to 0.204 ± 0.016 for EniLVP02. Meanwhile, in the biofilm destruction assay, the mixture treated with the phage lysate of EniLVP01 and EniLVP02 showed an absorbance of 0.139 ± 0.009 and 0.174 ± 0.026, respectively, compared to the untreated samples with an absorbance of 0.843 ± 0.0029. Both phages also demonstrated promising efficacy in reducing V. parahaemolyticus counts on retail shrimp matrices, with a bacterial reduction of 98% achieved using a cocktail both phages. Phage EniLVP01 and EniLVP02 exhibited stability across a wide range of pH (pH 4.0 – 9.0) and temperature (28 °C - 65 °C) conditions. Genomic sequencing revealed high similarity between EniLVP01 and EniLVP02, suggesting they may belong to the same species in the Caudovirales order or are very closely related despite originating from different sources. Importantly, the absence of lysogeny-related, antibiotic, and virulence genes in their genomes supports their safety for therapeutic use. These findings represent a significant advancement in understanding the potential of phage therapy in the battle against bacterial infections and antibiotic resistance issues within Malaysia generally, and within Sarawak specifically.